Influence of orthopaedic drilling parameters on temperature and histopathology of bovine tibia: An in vitro study - Karaca, F.; Aksakal, B.; Kom, M. (Elsevier Sci Ltd, 2011)
Orthopaedic drilling operations without optimum operating parameters by surgeons may cause bone defects such as bone fracture, cracks, osteolysis and tissue loss around the drilling zone. For the sake of optimum drilling parameters, an in vitro study was performed by considering the bone mineral density, bone sex, drill tip angle, drill speed, drill force and feed-rate. The specimens were taken from the drilled sites of fresh male and female calf tibias. The temperature changes at the drill site were investigated throughout the statistical and histopathological analysis. It was observed that the temperature increased with an increasing drill speed and decreased with high feed-rates and applied drill forces. The drilling temperatures of the female bovine tibias were found to be higher than that of the male tibias and the drill speed was found to be a significant parameter on the maximum temperature. Moreover, the maximum temperature increased with an increasing drill tip angle and bone mineral density. Therefore the bone quality around the drill site was found to be worse than the bone samples exposed to low temperatures. (C) 2011 IPEM. Published by Elsevier Ltd. All rights reserved.
Keywords: Bone drilling; Temperature; Orthopaedics; Histopathology